The Assembly Factor SDHAF2 Is Dispensable for Flavination of the Catalytic Subunit of Mitochondrial Complex II in Breast Cancer Cells - Bezawork-Geleta, Ayenachew; Dong, Lanfeng; Rohlena, Jakub; Neuzil, Jiri (The Journal of biological chemistry, 2016)
Mitochondrial complex II or succinate dehydrogenase (SDH) is at the crossroads of oxidative phosphorylation and the tricarboxylic acid cycle. It has been shown that Sdh5 (SDHAF2/SDH5 in mammals) is required for flavination of the subunit Sdh1 (SDHA in human cells) in yeast. Here we demonstrate that in human breast cancer cells, SDHAF2/SDH5 is dispensable for SDHA flavination. In contrast to yeast, CRISPR-Cas9 nickase-mediated SDHAF2 KO breast cancer cells feature flavinated SDHA and retain fully assembled and functional complex II, as well as normal mitochondrial respiration. Our data show that SDHA flavination is independent of SDHAF2 in breast cancer cells, employing an alternative mechanism.
Keywords: nádorové proteiny; flaviny; Electron Transport Complex II; Mitochondria; Cell Line, Tumor; posttranslační úpravy proteinů; Flavins; nádory prsu; Protein Processing, Post-Translational; mitochondriální proteiny; respirační komplex II; Mitochondrial Proteins; lidé; ženské pohlaví; Gene Knockdown Techniques; Breast Neoplasms; Humans; Neoplasm Proteins; genový knockdown; nádorové buněčné linie; Female; mitochondrie